Rapid and sustained decline in CXCL-10 (IP-10) annotates clinical outcomes following TNFα-antagonist therapy in hospitalized patients with severe and critical COVID-19 respiratory failure. Issue 1 (25th June 2021) - Hachem, Hilal; Godara, Amandeep; Schroeder, Courtney; Fein, Daniel; Mann, Hashim; Lawlor, Christian; Marshall, Jill; Klein, Andreas; Poutsiaka, Debra; Breeze, Janis L.; Joshi, Raghav; Mathew, Paul
Abstract: Background: A feedforward pathological signaling loop generated by TNFα and IFN-γ synergy in the inflamed lung, driving CXCL-10 (IP-10) and CXCL-9 chemokine-mediated activated T-cell and monocyte/macrophage tissue recruitment, may define the inflammatory biology of lethal COVID-19 respiratory failure. Methods: To assess TNFα-antagonist therapy, 18 hospitalized adults with hypoxic respiratory failure and COVID-19 pneumonia received single-dose infliximab-abda therapy 5 mg/kg intravenously between April and December 2020. The primary endpoint was time to increase in oxygen saturation to fraction of inspired oxygen ratio (SpO2/FiO2) by ≥50 compared to baseline and sustained for 48 h. Secondary endpoints included 28-day mortality, dynamic cytokine profiles, secondary infections, duration of supplemental oxygen support, and hospitalization. Findings: Patients were predominantly in critical respiratory failure (15/18, 83%), male (14/18, 78%), above 60 years (median 63 years, range 31–80), race-ethnic minorities (13/18, 72%), lymphopenic (13/18, 72%), steroid-treated (17/18, 94%), with a median ferritin of 1953 ng/ml. Sixteen patients (89%) met the primary endpoint within a median of 4 days; 14/18 (78%) were discharged in a median of 8 days and were alive at 28-day follow-up. Three deaths were attributed to secondary lung infection. Mean plasma IP-10 levels declined sharply from 9183 to 483 pg/ml at Day 3 and 146 pg/ml at Day 14/discharge. Significant Day 3 declines in IFN- γ , TNFα, IL-27, CRP, and ferritin occurred. IP-10 and CXCL-9 declines were strongly correlated among patients with lymphopenia reversal (Day 3, Pearson r : 0.98, P -value 0.0006). Interpretation: Infliximab-abda may rapidly abrogate pathological inflammatory signaling to facilitate clinical recovery in severe and critical COVID-19.